Impact of intermolecular vibrational coupling effects on the sum-frequency generation spectra of the water/air interface - Kaliannan, Naveen Kumar; Aristizabal, Andres Henao; Wiebeler, Hendrik; Zysk, Frederik; Ohto, Tatsuhiko; Nagata, Yuki; Kühne, Thomas D. (Molecular Physics, 2020)
We have examined the impact of intermolecular vibrational coupling effects of the O-H stretch modes, as obtained by the surface-specific velocity-velocity correlation function approach, on the simulated sum-frequency generation spectra of the water/air interface. Our study shows that the inclusion of intermolecular coupling effects within the first three water layers, i.e. from the water/air interface up to a distance of 6 Å towards the bulk, is essential to reproduce the experimental SFG spectra. In particular, we find that these intermolecular vibrational contributions to the SFG spectra of the water/air interface are dominated by the coupling between the SFG active interfacial and SFG inactive bulk water molecules. Moreover, we find that most of the intermolecular vibrational contributions to the spectra originate from the coupling between double-donor water molecules only, whereas the remaining contributions originate mainly from the coupling between single-donor and double-donor water molecules.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Partially adiabatic centroid molecular dynamics; sum-frequency generation; water/air interface